Towards an effective occupational health and safety culture: A multiple stakeholder perspective - Claxton, Garry; Hosie, Peter; Sharma, Piyush (Elsevier, 2021)
Introduction: This paper uses an extensive review of the safety culture literature to identify three key themes (a) role of new employees, (b) absence of a pro-active approach, and (c) need for a ‘No-blame’ culture, and explores their impact on the occupational health and safety culture (OHS).